A REVIEW OF IMAGE MINING - FACE DETECTION AND RECOGNITION - H S, Bhaskar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Transformation of a picture into digital form to function on and improve the image is image processing. Face is a unique identification of every personality. There is denial disturb complimentary and a troublesome way of recognizing every person. Face identification is a procedure of capturing pictures in remoteness. The face identification involves face alignment and feature mining. The research paper elaborates the process of mining the characteristics and recognizing a face digitally by Convolution Neural Network and Viola Jones process. Pre-processing is minimal in Convolution Neural Network. Investigation is slow but uncovering is fast in Viola and Jones process. Face uncovering is done by OpenCV. Face identification uses the trained structures stored to differentiate various faces. Viola and Jones procedure is worn to identify the appearance and crop the facial region. Convolution Neural Network is an important verification module comprising identification, extraction, and acknowledgement. This research paper develops a novel technique for identification of an individual by recognizing the face.